Research on Clustering Management of Power Distribution Internet of Things Based on Trusted Blockchain. Issue 5 (January 2021) - Sun, Yue; Chen, Wei; Chen, Leran; Li, Min
Abstract: Since the topological structure of power distribution Internet of Things is getting more and more complicated, and the amount of new services, such as remote dynamic monitoring and two-way real-time interaction, has been increasing, it is urgent and necessary to study the clustering management technology of power distribution Internet of Things combined with its running scenarios, security requirements and dynamic access characteristics. In this paper, a clustering security management scheme of power distribution Internet of Things based on trusted blockchain is proposed. The clustering management and data communication of power distribution Internet of Things are conducted based on trusted blockchain, which can improve the security of data interaction.